Epidemiology of congenital malformations in Sri Lanka - Corea, S..M..X (My University, 1982)
The study provides base-line data for the incidence of various types of malformation and their possible association with a etiological influences like race, region, consanguinity etc. The findings gave support to many views based on previous evidence while they are not compatible with some others e.g. the highest rate of anencephalic in the wet zone area (zone 3) with better socio economic conditions was contrary to the findings of Fredrick’s (1970) who found the incidence was highest in the lowest socio-economic groups. In the case of male: female ratio for central nervous system malformations there was a marked difference between the results of the W.H.O. study (Stevenson et al 1966)- where the male : female ratio was 1:3 and in the present study where the ratio was 2:1. It is hoped that this study would be the first in a series of many more studies of this nature which would provide valuable information on congenital malformation